Effect of thoracic epidural analgesia on clinical outcomes following transapical transcatheter aortic valve implantation. Issue 21 (11th July 2012) - Amat-Santos, Ignacio J; Dumont, Eric; Villeneuve, Jacques; Doyle, Daniel; Rheault, Michel; Lavigne, Dominique; Lemieux, Jerôme; St-Pierre, André; Mok, Michael; Urena, Marina; Nombela-Franco, Luis; Blackburn, Steve; et al.
Abstract : Objective: To determine the impact of perioperative thoracic epidural analgesia (TEA) on acute and late outcomes following transapical transcatheter aortic valve implantation (TA-TAVI). Patients and intervention: A total of 135 consecutive patients who underwent TA-TAVI were included. All patients received catheter-based pain control, either via TEA (TEA group, n=74) or intercostal local analgesia with a catheter placed at the surgical incision site (non-TEA group, n=61), depending on the preference of the anaesthesiologist responsible for the case. Main outcome measures: Pain level during early postoperative period (verbal rating scale from 1 to 10), 30-day/in-hospital complications and mortality, and 1-year mortality. Results: There were no differences in baseline or procedural characteristics between groups except for a lower left ventricular ejection fraction in the TEA group. The maximal pain score related to thoracotomy in the postoperative period was higher in the non-TEA group as compared with the TEA group (4 (IQR: 3–5)) vs 2 (IQR: 1–3), p<0.001). Non-TEA was associated with a higher rate of pulmonary complications (p<0.05 for nosocomial pneumonia, reintubation and tracheostomy). The 30-day/in-hospital mortality rate was higher in the non-TEA group (22.9% vs 2.7% in the TEA group, p<0.001). At 1-year follow-up, overall mortality remained higher in the non-TEA group (31.1%) compared with the TEA group (10.8%), p=0.005. Similar periprocedural and late results were obtained in a propensity score-matched analysis that included 100 matched patients. In the multivariable analysis, STS score (p=0.027) and absence of TEA (p=0.039) were independent predictors of increased cumulative late mortality. Conclusions: TEA provided superior analgesia following TA-TAVI, and was associated with a dramatic reduction in periprocedural respiratory complications, and both, short- and long-term mortality. These results highlight the importance of obtaining optimal analgesia following TA-TAVI to improve the results associated with this procedure.